A decomposition analysis of CO2 emissions: evidence from Malaysia's tourism industry. Issue 3 (3rd May 2016) - Ng, Tuan Hock; Lye, Chun Teck; Lim, Ying San
ABSTRACT: The most important question raised from issues of environmental degradation is how economic activities bring about changes that will result in pollution. In the pursuit of tourism economy, contrary to popular interest, the travel and tourism (T&T) industry may cause environmental damages through the emissions of carbon dioxide (CO2 ) from energy consumption in areas such as transportation and delivery of amenities. Given this major concern, this paper attempts to investigate the linkage between tourism and CO2 emissions in Malaysia between 1981 and 2011. In particular, this study fills the knowledge gap by taking a closer look at the impact of international tourist arrivals on CO2 emissions by sector – electricity and heat generation and transport. Results from the bound test method suggest that there exists a long-run relationship among the variables under consideration when CO2 emissions become the dependent variable. The original result is similarly robust to alternatives, which are CO2 emissions from sectors of electricity and heat generation and transport. Furthermore, the vector error correction model causality analysis indicates a causal relationship between tourism and CO2 emissions by transport and electricity and heat generation. Subsequently, several tourism-related policies are drawn from these findings.